Factors influencing the adoption of internet banking in Malaysia - Queenie Sinti (2004)
This is an empirical research and was carried out to determine the factors influencing the adoption of Internet banking by Malaysian consumers. The sample from this survey was drawn from individual residents in Malaysia. A research framework based on the theory of planned behavior and the diffusion of innovations theory known as the decomposed theory of planned behavior (DTPB) were used to identify the attitudinal, social influence and perceived behavioral control factors that would influence the adoption of Internet banking. An online questionnaire was used in this research and respondents were approached through extensive personalized email invitations as well as postings to the newsgroups. The results of this research revealed that attitudinal and perceived behavioral control factors, rather than social influence play a significant role in influencing the intention to adopt Internet Banking services. In particular only complexity, trialability, banking needs, government support and self-efficacy were found to influence the intention to adopt Internet Banking services. Details of the results, implications of the findings, limitations of the study, future research directions, and conclusions are presented.